2019
DOI: 10.1007/s10880-019-09644-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Sociodemographic, Clinical, and Psychological Variables to Quality of Life in Women with Cervical Cancer in the Follow-Up Phase

Abstract: This study evaluates the contribution of sociodemographic, clinical, and psychological variables to quality of life (QoL) of women with cervical cancer in the follow-up phase. This cross-sectional study, conducted at the Portuguese Oncology Institute of Lisbon, included 200 women with cervical cancer during follow-up. Patients were assessed on QoL (EORTC QLQ-C30), body image and specific symptoms (EORTC QLQ-CX24), psychological morbidity (HADS), social support (SSSS), emotional expression (CECS), and spiritual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
1
7
0
1
Order By: Relevance
“…Cancer reduces quality of life considerably ( Pirri et al, 2013 ), due to being a disease in itself and the limitations experienced by patients ( Mc Caughan et al, 2013 ). Such decrease in quality of life is caused by a variety of factors and it has been observed in every type of cancer ( Barbus et al, 2018 ; Adamowicz et al, 2020 ) and all the stages of the medical process ( Lopes et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer reduces quality of life considerably ( Pirri et al, 2013 ), due to being a disease in itself and the limitations experienced by patients ( Mc Caughan et al, 2013 ). Such decrease in quality of life is caused by a variety of factors and it has been observed in every type of cancer ( Barbus et al, 2018 ; Adamowicz et al, 2020 ) and all the stages of the medical process ( Lopes et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the women interviewed mentioned lack of social support after they were diagnosed and during treatment, which has been cited previously as a crucial barrier to QoL during and after experience with cancer (Khalil et al, 2015;Lopes et al, 2020;Shinan-Altman et al, 2022;Sun et al, 2021;Tejada et al, 2015;Yagmur & Duman, 2016). Research demonstrates that poor social support during cancer is correlated with significantly greater distress and feelings of abandonment as well as more maladaptive coping methods (Levkovich et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Spirituality has been shown to contribute significantly to QoL (Garssen et al, 2015; Khalil et al, 2015). Most of the participants in our study were college-educated, which has also been shown to contribute significantly to QoL (Lopes et al, 2020; Mujahadatuljannah, 2019; Reese et al, 2017; Sun et al, 2021). All of the women were mothers and expressed that they gathered strength to fight their cancer for their children, who were incredibly important to them.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Patients immersed in bad emotions paid less attention to disease management, on the other side, bad emotions might affect the judgment of self-worth, resulting in the reduction of self-identity. All of these led to the decline of patients' QoL [41].…”
Section: Discussionmentioning
confidence: 99%